A comprehensive review of yttrium aluminum nitride: crystal structure, growth techniques, properties, and applications - Afshar, N.; Yassine, M.; Ambacher, O. (Frontiers in Materials, 2025)
YAlN has emerged as a wide band gap semiconductor with high potential to compete with ScAlN in industrial applications. Theoretical predictions about YAlN’s material properties have been the main motivation for conducting experimental investigations and verify simulated results. However, several challenges have been faced in experimental studies on YAlN that contradict theoretical data, especially when trying to reach higher alloy concentrations. This work presents a systematic review analyzing different material properties including structural characterization, elastic properties, and thermal features. It combines all available experimental data on the growth and reported material parameters, such as band gap, lattice parameters, and electrical properties with the aim of introducing a new motivation to further study YAlN’s potential in various fields of device applications. The review provides a comprehensive overview on the current state of knowledge on YAlN, highlighting the discrepancies between theoretical predictions and experimental results. By providing information from multiple studies, this work offers valuable insights into the challenges and opportunities associated with YAlN development, paving the way for future research directions and potential industrial applications of this promising wide band gap semiconductor.